The absence of formal work experience may affect the rate of cognitive decline in older adult women: findings from the health and retirement study - Daya K. Grewal; Daya K. Grewal; Molly A. Patapoff; Molly A. Patapoff; Victoria Liou-Johnson; Victoria Liou-Johnson; Victoria Liou-Johnson; Maheen M. Adamson; Maheen M. Adamson; Maheen M. Adamson; Dylan J. Jester (Frontiers in Global Women's Health, 2024)
ObjectiveThis study investigated the relationship between years of employment and cognitive health among older non-Latinx Black, Latinx, and non-Latinx White women. We hypothesized that women who had never been formally employed (i.e., zero years of formal work experience) would exhibit a pronounced cognitive decline.MethodsOur study included 5,664 older adult women from the Health and Retirement Study (2010–2016) aged 65–101 (M = 75.41). Out of 5,664 participants, 850 identified as non-Latinx Black, 475 identified as Latinx, and 4,339 identified as non-Latinx White. Furthermore, 5,292 women indicated having a professional employment history of at least one year, whereas 372 women reported no formal work experience. The Telephone Interview for Cognitive Status-27 (TICS-27) was used to assess cognitive performance. Linear mixed effects models were conducted to assess whether employment history was associated with the rate of cognitive decline.ResultsIn all three racial and ethnic groups, lower age, higher education, greater number of years worked, fewer chronic conditions, and greater household income were associated with better cognitive performance at baseline (p < .05). Additionally, women who had not worked in any formal capacity had a lower baseline cognitive performance (p < .001) and a more extreme decline in cognitive performance over time (p = .04).ConclusionIn conclusion, we found that women without any formal work experience performed lower at baseline and experienced a steeper cognitive decline over time. These findings underscore the need to further explore the complex interrelationships between employment duration and cognitive trajectories, especially among older women and those from different racial and ethnic backgrounds.